Analysis of Differentiated Learning Using Learning Technology Based on Discovery Learning Model in Elementary School - Ihtasya Aulia Fathimatuz Zahra; Muhammad Aunur Rahman Suja'; Varicha Candra Dinata; Izza Mantasya Naufal; Bakti Fatwa Anbiya (Research Journal on Teacher Professional Development, 2023)
This research aims to analyze differentiated learning approaches through the use of learning technology based on the Discovery Learning model at the elementary school level. This research uses the literature review method, in which various literature sources related to the use of learning technology and the Discovery Learning model in differentiated learning are explored, analyzed, and synthesized to get a comprehensive picture of this topic. The results of the literature review show that the use of learning technology based on the Discovery Learning model has great potential in enhancing the learning potential of differentiation in elementary schools. This approach can stimulate students' interest and engagement in learning, as well as encourage the development of critical, collaborative and creative thinking skills. Learning technologies such as interactive software, educational applications and multimedia aids can facilitate a more engaging and personalized learning experience for each student.